The mechanism and origin of selectivities for NHC-catalyzed synthesis of axially chiral benzothiophene/benzofuran-fused biaryls. Issue 8 (8th February 2022) - Zhang, Jiaming; Qiao, Qinyu; Wu, Zhoujie; Pang, Zhou; Shi, Qianqian; Wang, Yanyan; Qiao, Yan; Wei, Donghui
Abstract : DFT calculations were performed to investigate the actual mechanism of organocatalytic intermolecular [2 + 4] cyclization for the synthesis of axially chiral benzothiophene-fused biaryls using enal and 2-benzyl-benzothiophene-3-carbaldehyde. Abstract : By performing density functional theory (DFT) calculations, we investigated and identified the fundamental pathway for N-heterocyclic carbene (NHC)-catalyzed synthesis of axially chiral benzothiophene-fused biaryls using enal and 2-benzyl-benzothiophene-3-carbaldehyde, which includes (1) nucleophilic attack on enal by the organocatalyst NHC, (2) [1, 2]-proton transfer, (3) oxidation, (4) stereoselective formation of the C–C σ bond, (5) intramolecular [2 + 2] cycloaddition, (6) dissociation of NHC, (7) release of CO2, and (8) transformation to axial chirality. Moreover, the calculated results can reasonably explain the observed chemo- and stereoselectivities for the formation of both benzothiophene/benzofuran-fused biaryls in these kinds of reactions. Further non-covalent interaction (NCI) and atoms-in-molecules (AIM) analyses demonstrate that the hydrogen bond interactions are responsible for the stability of key stereoselective transition states. This work would be useful for understanding the origin of stereoselectivity of NHC-catalyzed intermolecular cyclization reactions for the synthesis of axially benzothiophene/benzofuran-fused biaryl compounds.